Teaching knowledge and wisdom in Chemistry teaching: what does Dissertations and Theses Show? (Research, Society and Development, 2020)
This research consisted of the analysis of Dissertations and Theses (DTs) that investigated both teaching knowledge and/or teaching wisdom in Chemistry Teaching from 2010 to 2019 available in Biblioteca Digital Brasileira de Teses e Dissertações—BDTD (Brazilian Digital Library of Theses and Dissertations) and Catálogo de Teses e Dissertações da Capes ((Coordenação de Aperfeiçoamento Pessoal de Nível Superior) (Capes Dissertations and Theses Catalog). This research is seen as a state of knowledge. The search terms applied were ‘teaching knowledge’ and ‘teaching wisdom’. At first, 1.125 DTs were found containing the given search terms. However, only 64 investigated teaching knowledge and wisdom in Chemistry Teaching. The analysis of the DTs was performed through the investigation of content and emerging categories. Out of the 57 DTs, 15,6% based on teaching knowledge, 28% based on teaching wisdom, 36% distinguished the concepts of knowledge and wisdom, and 20,3% did not distinguish them. The theoretical literature review of those studies relied mostly on the works of Clermont Gauthier, Maurice Tardif, and Lee Shulman. The studies focused mainly on investigating teaching wisdom to the detriment of teaching knowledge.